Systematics and biogeography of the subfamily Tillinae (Coleoptera: Cleridae) in the New World - Burke, Alan Fernando (Kansas State University, 2017)
The subfamily Tillinae is composed of approximately 700 species with a cosmopolitan distribution. In the New World, the group is composed of 164 species classified in 12 genera. Tillinids are generalist predators of other insects but there is some ecological specificity among related species (i.e. predation on bark and wood-boring beetles). The systematics and biogeography of the subfamily have never been studied. Several genera inhabiting the New World have never been revised, a number of species in the group were described more than 50 years ago, and many of those descriptions were inadequate. Consequently, I present here the first systematic and biogeographic study of the Tillinae in the New World. First, a revision of the New World Tillinae, excluding the species-rich Cymatodera Gray is presented. The diagnosis and redescription of 26 species from 11 of the 12 tillinid genera from the New World are given; a new synonym, keys to genera and species, and distribution maps for all the genera treated here are also given. Collection data for all species examined is presented. A new genus was described based on this work in a separate publication. Second, a phylogenetic analysis based on 91 morphological characters and a molecular phylogenetic study based on the analysis of three loci, 16S rDNA, COI and 28S rDNA, for 89 taxa in 37 genera is presented. Results were compared with previous classifications at the subfamily level. Results are generally consistent, recovering Tillinae as a derived and monophyletic group; Old World tillinids were found to be basal groups and sister to New World Tillinae; the New World genus Onychotillus was found to be sister to remaining New World Tillinae; the small genera Barrotillus, Callotillus, Monophylla and Neocallotillus were recovered as basal lineages within the New World Tillinae with intergeneric relations not fully resolved; and the species-rich Cymatodera was found to be a paraphyletic group by the inclusion of the genera Araeodontia, Bogcia, Cymatoderella and Lecontella. A phylogeny was also constructed based on a concatenated molecular + morphology dataset; the topology obtained from this analysis is generally consistent with the molecular- and morphology-based phylogenies, separately. Finally, a hypothesis of the historical biogeography of Cymatodera, the most species-rich genus in the subfamily Tillinae, is presented. The genus is endemic to, but broadly distributed, in the New World. The principal aim of the study was to infer the age of origin of the group. Hypotheses regarding the center of origin, patterns of distribution, and putative processes that led to the widespread distribution of this group are presented. A phylogenetic analysis of 50 New World tillinid species was constructed using the markers 16S rDNA, COI, and 28S rDNA. A relaxed molecular clock calibrated with three secondary dates derived from other time-calibrated phylogenies is presented. Biogeographic processes were studied using a Bayesian Binary Markov Chain Monte Carlo analysis in the software Reconstruct Ancestral State in Phylogenies. Results obtained here indicate that Cymatodera emerged approximately 71.5 MYA during the mid-Cretaceous in what is now southwestern USA and northern Mexico. Two major dispersal events occurred during the evolution of the Cymatodera lineage, the first, an eastern migration process, and the second, a southern migration event, the latter route had a greater impact on the diversification of the group. Overall, this research provides a solid foundation for studying the systematics and biogeography of the world Tillinae. Species with recent shared ancestry tend to have similar functional traits for exploiting similar resources. A robust phylogenetic analysis can help elucidate prey preferences or other biological traits for species whose biology is poorly known. This study will also serve as a foundation to investigate broader evolutionary aspects of the subfamily, such as predator-prey associations, mimicry, and the emergence and diversification of pheromone reception, one of the most interesting aspects within the evolutionary history of the group.
Keywords: Systematics; Biogeography; Cleridae; Tillinae; Cymatodera